Bioactive compounds as an alternative for drug co-therapy: Overcoming challenges in cardiovascular disease prevention. Issue 6 (13th April 2018) - Scolaro, Bianca; Soo Jin Kim, Hellen; de Castro, Inar Alves
ABSTRACT: Different pharmacological interventions have been applied with success to reduce the progression of atherosclerosis. However, many patients are not good responders or must interrupt treatment due to adverse effects. Bioactive compounds such as omega-3 fatty acids (n-3 FA), plant sterol esters (PSE) and phenolic compounds (PHC) are natural molecules with great potential to reduce the atherosclerosis burden by reducing inflammation, LDL cholesterol (LDL-C) and oxidative stress, respectively. Although their physiological effects on biomarkers are much lower than those expected by drugs used for the same purpose, bioactive compounds can easily be incorporated into the daily diet and present no adverse effects. However, little is known about the combination of n-3 FA, PSE, PHC, and drugs in atherosclerosis progression. This review article summarizes potential effects of co-therapies involving n-3 FA, PSE, and PHC combined with major hypolipidemic drugs on atherosclerosis biomarkers and clinical outcomes. Evidence of additive and/or complementary effects regarding drugs action reveals possible roles for bioactive compounds in disease management. Pharmaceutical companies, physicians, and food scientists should be prepared to better understand this type of interaction and its consequences in terms of efficacy and life quality.